The physicochemical and antioxidant properties of double-boiled kelulut honey - A. Rahman, Nur Atikah (2019)
Kelulut honey is a unique Malaysian food that has beneficial components and high potential in many health aspects. In commercial processing plant, honey is usually subjected to thermal treatment, where its quality is compromised due to unstable and thermolabile components. Therefore, double boiling was chosen as it does not exert significant heat, thus minimizes damage done. The quality was determined after treated by double boiling technique at optimized condition. Three different sources of Kelulut honey based on the main types of foods consumed by the bees (Coconut, Multifloral and Wild Flowers) were tested. Kelulut honey samples were subjected to an optimized condition at 60 °C for 35 minutes. Thermal treatment at the same condition was conducted for comparison purpose. The results showed that double boiling treatment increased the total phenolic content of Kelulut-C honey significantly, from 2430.78 ± 12.24 to 2711.10 ± 23.00 mg GAE/100 g. The treatment also significantly increased the brown pigment for both Kelulut-C and Kelulut-W honey by 11.11 ± 0.00% and 27.27 ± 0.00%, respectively. Whereas, the pH and moisture content of all samples remain unchanged with no formation of hydroxymethylfurfural (HMF) was observed. A preliminary four-week storage study showed that double boiling treatment improves physicochemical properties of Kelulut honey as compared to the untreated samples for all three types of Kelulut honey tested. Meanwhile, a room temperature (27 °C) condition leads to an improvement of antioxidant properties as compared to cold temperature (4 °C). In conclusion, double boiling treatment has established itself as a good alternative processing method for Kelulut honey, hence increasing the possibility to bring forward Kelulut honey as a unique source for the application in food and beverages industries.